Broadband Reflectometry for Enhanced Diagnostics and Monitoring Applications - Cataldo, Andrea; De Benedetto, Egidio; Cannazza, Giuseppe (Lecture Notes in Electrical Engineering, 2011)
This book is dedicated to the adoption of broadband microwave reflectometry (BMR)-based methods for diagnostics and monitoring applications. This electromagnetic technique has established as a powerful tool for monitoring purposes; in fact, it can balance several contrasting requirements, such as the versatility of the system, low implementation cost, real-time response, possibility of remote control, reliability, and adequate measurement accuracy. Starting from an extensive survey of the state of the art and from a clear and concise overview of the theoretical background, throughout the book, the different approaches of BMR are considered (i.e., time domain reflectometry - TDR, frequency domain reflectometry - FDR, and the TDR/FDR combined approach) and several applications are thoroughly investigated. The applications considered herein are very diverse from each other and cover different fields. In all the described procedures and methods, the ultimate goal is to endow them with a significant performance enhancement in terms of measurement accuracy, low cost, versatility, and practical implementation possibility, so as to unlock the strong potential of BMR.